Stakeholder Analysis of Mangrove Management in Tangerang Coastal District, Banten, Indonesia - Muzani, Muzani (SOSIOHUMANIKA, 2014)
ABSTRACT: Mangrove ecosystems have the important ecological, economic, and social functions that need consideration in coastal development. Mangrove forests provide essential functions and services to coastal populations, such as protection of the coastal zone and a variety of timber and non-timber forest products. However, mangroves in Tangerang coastal district, Banten, Indonesia are being degraded by human activities brought about by a range of stakeholders. The complexity of stakeholders creates problems through various government departments having overlapping jurisdictions. This study aimed to develop strategies to increase the role of stakeholders in the management of mangrove ecosystems in Tangerang Regency. Stakeholders were identified from interviews obtained through a snowball sampling method. In the coastal district of Tangerang, there are 12 different types of stakeholders involved in mangrove management from government to local people. Each of these stakeholders has an interest and influence in mangrove management. Lack of coordination among stakeholders often results in the variety of management activities. The study recommends the strategies to increase the role of stakeholders through improved coordination, information, and collaboration among stakeholders.KEY WORD: Stakeholder, management, mangrove, Tangerang coastal district, government, local people, coordination, information, and collaboration.Â RESUME: âAnalisis Pemangku Kepentingan tentang Pengelolaan Hutan Bakau di Daerah Pesisir Tangerang, Banten, Indonesiaâ. Ekosistem hutan bakau memiliki fungsi penting secara ekologis, ekonomis, dan sosial yang perlu dipertimbangkan dalam pembangunan daerah pesisir. Hutan bakau berfungsi dan melayani secara esensial bagi masyarakat pesisir, seperti perlindungan wilayah pantai serta variasi produk hutan timber dan bukan timber. Bagaimanapun, hutan bakau di daerah pesisir Tangerang mengalami kerusakan oleh aktivitas manusia. Banyaknya jumlah pemangku kepentingan yang berkepentingan dengan hutan bakau sering menciptakan masalah melalui lembaga-lembaga pemerintah dan mengakibatkan tumpang-tindih kewenangan. Penelitian ini bertujuan mengembangkan strategi untuk meningkatkan peran para pemangku kepentingan dalam pengelolaan ekosistem hutan bakau di Kabupaten Tangerang. Para pemangku kepentingan diidentifikasi dari wawancara yang diperoleh melalui sebuah metode sampel efek bola salju. Di daerah pesisir Tangerang, terdapat 12 pihak pemangku kepentingan berbeda-beda, yang terlibat dalam pengelolaan hutan bakau mulai dari pemerintah hingga masyarakat setempat. Masing-masing pihak memiliki kepentingan dan pengaruh dalam pengelolaan hutan bakau. Kurangnya koordinasi antar pemangku kepentingan sering menyebabkan keragaman dalam kegiatan pengelolaan. Penelitian ini merekomendasikan strategi untuk meningkatkan peran para pemangku kepentingan melalui peningkatan koordinasi, informasi, dan kolaborasi diantara mereka.KATA KUNCI: Pemangku kepentingan, pengelolaan, hutan bakau, daerah pesisir Tangerang, pemerintah, masyarakat setempat, koordinasi, informasi, dan kolaborasi.About the Author: Muzani, M.Si. is a Doctoral Candidate at the IPB (Institut Pertanian Bogor or Bogor Agricultural University), Jalan Lingkar Akademik, Kampus IPB Darmaga, Bogor, West Java, Indonesia. For academic interests, he can be contacted via e-mail at: muzaniunj@yahoo.co.idHow to cite this article? Muzani. (2014). âStakeholder Analysis of Mangrove Management in Tangerang Coastal District, Banten, Indonesiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.7(2) November, pp.257-268. Bandung, Indonesia: Minda Masagi Press, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112.Chronicle of the article: Accepted (November 30, 2013); Revised (June 20, 2014); and Published (November 20, 2014).